Exploratory analysis of learners’ motivation on learning Mathematics in Philippines - Campanilla, Norveen S. (Goodwood Publishing, 2024)
Purpose: The primary objective of this study was to investigate how motivation explains learners’ performance in mathematics. Research methodology: This study analyzed learners' age, sex, parents' educational attainment, siblings, occupation, and motivation using Mubeen and Reid's (2014) measurement. It also tested their relationship with mathematics achievement, and determined a regression model for predicting high school mathematics performance. Results: The study revealed a male-dominated population of Grade 9 learners at Matucay National High School, with satisfactory mathematics performance and four siblings. They align their personal goals with learning, and their motivation is crucial for positive study habits and academic achievement, particularly in mathematics. Limitations: This study examined learner motivations in mathematics among Grade 9 students at Matucay National High School, focusing on factors such as expectations, learning outcomes, development track, future career success, and test-taking ability. Contribution: Given that the pandemic has had a significant impact on the municipality, this study will benefit students by offering strategies for staying motivated to learn mathematics to manage and regulate the impact of the outbreak on their academic performance. Novelty: This study explores learners' motivation in mathematics among Grade 9 students at Matucay National High School in the Philippines. It uses Mubeen and Reid's motivation measurement and analyzes demographic factors, motivational attributes, and their correlations with academic achievement. The study revealed that mothers' educational attainment and motivation significantly predicted their mathematics performance. This study provides insights into improving mathematics education and learner outcomes.